Impact of menstrual cycle phase and oral contraceptives on sleep and overnight memory consolidation. (21st December 2020) - Plamberger, Christina Paula; Van Wijk, Helen Elisabeth; Kerschbaum, Hubert; Pletzer, Belinda Angela; Gruber, Georg; Oberascher, Karin; Dresler, Martin; Hahn, Michael Andreas; Hoedlmoser, Kerstin
Abstract: Sleep spindles benefit declarative memory consolidation and are considered to be a biological marker for general cognitive abilities. However, the impact of sexual hormones and hormonal oral contraceptives (OCs) on these relationships are less clear. Thus, we here investigated the influence of endogenous progesterone levels of naturally cycling women and women using OCs on nocturnal sleep and overnight memory consolidation. Nineteen healthy women using OCs (MAge = 21.4, SD = 2.1 years) were compared to 43 healthy women with a natural menstrual cycle (follicular phase: n = 16, MAge = 21.4, SD = 3.1 years; luteal phase: n = 27, MAge = 22.5, SD = 3.6 years). Sleep spindle density and salivary progesterone were measured during an adaptation and an experimental night. A word pair association task preceding the experimental night followed by two recalls (pre‐sleep and post‐sleep) was performed to test declarative memory performance. We found that memory performance improved overnight in all women. Interestingly, women using OCs (characterized by a low endogenous progesterone level but with very potent synthetic progestins) and naturally cycling women during the luteal phase (characterized by a high endogenous progesterone level) had a higher fast sleep spindle density compared to naturally cycling women during the follicular phase (characterized by a low endogenous progesterone level). Furthermore, we observed a positive correlation between endogenous progesterone level and fast spindle density in women during the luteal phase. Results suggest that the use of OCs and the menstrual cycle phase affects sleep spindles and therefore should be considered in further studies investigating sleep spindles and cognitive performance.